LEARNING EFFECT OF CITIZENSHIP EDUCATION STUDENTS IN APPLICATION OF CHARACTER VALUE - Mareta Rahma Silvia; Irawan Suntoro; Yunisca Nurmalisa (FKIP Unila, 2012)
The purpose of this study is to investigate and analyze the influence of learning of civic education on the application value of the character of students in SMAN 1 Terbanggi Beasar Lampung regency middle of the school year 2012/2013. The research method used in this research is correlational. The sample in this study amounted to 85 people. Data analysis using Chi Square. The results showed that there are significant civic education for students in the application of value character SMAN 1 Terbanggi Besar Central Lampung regency school year 2012/2013 in the medium category.Keywords: learning citizenship education, application value character, civic education